Pre-Clinical Studies of Inactivated Polyvalent HFRS Vaccine - Dzagurova, Tamara K.; Siniugina, Alexandra A.; Ishmukhametov, Aidar A.; Egorova, Maria S.; Kurashova, Svetlana S.; Balovneva, Maria V.; Deviatkin, Andrey A.; Tkachenko, Petr E.; Leonovich, Oksana A.; Tkachenko, Evgeny A. (Frontiers in Cellular and Infection Microbiology, 2020)
Hemorrhagic fever with renal syndrome (HFRS) is the most common natural focal disease in the Russian Federation with about 6 - 12 thousand cases annually. 97.7% of all HFRS cases in Russia caused by the Puumala virus, 1.5% – by the Hantaan, Amur, Seoul viruses and about 0.8% by the Kurkino and Sochi viruses. There are no licensed vaccines for the prevention of HFRS in the European Region; there are no specific therapeutic to treat orthohantavirus infections. Here we report the results of candidate polyvalent HFRS vaccine preclinical studies. The vaccine was produced on the basis of 3 viruses: Puumala, strain PUU-TKD/VERO, Hantaan, strain HTN-P88/VERO and Sochi, strain DOB-SOCHI/VERO. These viruses were inactivated with β-propiolacton, purified by gel filtration and aluminum hydroxide sorbed. 18-20 g female BALB/c mice were immunized intramuscularly 2 or 3 times with a 2-week intervals and blood was taken 2 weeks after immunization. FRNT50 performed for virus specific antibodies determination. ELISA kits (Bender MedSystems, Cusabio) were used for the cytokines IL-1β, IL-12, INF-ɣ detection. Neutralizing antibodies geometric mean titers to the Puumala, Hantaan and Sochi viruses were: 9.22 ± 0.31, 9.17 ± 0.26, 8.96±0.34 log2/ml. Up to 1/32 vaccine dilution neutralizing antibodies were identified in 10/10 immunized mice in titer ≥ 3,32 log2/ml. IL-12 and INF-ɣ increased after immunization in average 5.5 and 2.8 times respectively, that reflects the Th1 type immunity stimulation. IL-1β slightly increased, that may suggest vaccine low reactogenicity. According to our preclinical investigations candidate polyvalent HFRS vaccine elicits harmonious immune response to the Puumala, Hantaan and Sochi viruses.